The Implementation of Group Investigation Cooperative Learning to Improve Students Affective Ability of VIIA Class SMP Negeri 16 Surakarta Class Year 2010/2011 - Yuliana Yuliana; Slamet Santosa; Harlita Harlita (BIO-PEDAGOGI, 2013)
The purpose of the research is to increase students affective ability of class VII  A  SMP  Negeri 16  Surakarta  through the implementation of  Cooperative Learning by Group Investigation method on Environmental pollution material. This research is a  Classroom Action Research with two cycles of action. Each cycle  consisting of four  phases  which is  planning,  acting, observing,  and reflecting. Observational  data obtained from the  questionaire, observation, and interview. Subjects were students of class VII A SMP Negeri 16 Surakarta. Data validation is use triangulation methods.  Technical analysis  of data is technical descriptive. The result of this research showed that averagely assesses  percentage each indicator of students affective responses questionnaire on pre cycle is 66,39 %, first cycle is 76,95  %    and second cycle  is   84,01  %  (worked up 7,06  %). Meanwhile on a percentage point each indicator which is gotten from observation result students affective responses for pre cycle is 48,52%, first cycle  is  72,22 % and second cycle is 82,35 % (worked up 10,13% ). The students interview result are 97,22% students interested in implementation on Group Investigation method, 80,56% students asking question, 83,33% students respond the idea from another student, and 83,33% students find out a problem solving. The  result  showed  that  Cooperative  Learning  by  Group Investigation could increase students affective ability of class VII A SMP Negeri 16 Surakarta class year 2010/2011 in Biological learning. Key Words: Cooperative learning, Group Investigation, Students Affective Ability